Extraction of platinum and gold from copper anode slimes by a process of chlorinating roasting followed by chlorinating leaching - Wang S.; Li L.; Wang S.-D.; Wang H.; Wu G.-D. (Journal of Mining and Metallurgy. Section B: Metallurgy)
A novel process of chlorinating roasting followed by chlorinating leaching to extract platinum and gold from copper anode slimes was proposed in this research. Results of thermodynamic analysis and experimental research showed that the platinum was chlorinated into PtCl2 while the gold existed in the form of metallic Au during the roasting process. With the copper anode slime being directly leached using a traditional process, the Pt recovery rate was low and came to 80.72%. After the roasting process with sodium chloride and concentrated sulfuric acid in oxygen atmosphere, the recovery rate of Pt increased to a value around 95%. Moreover, with excessive addition of concentrated sulfuric acid, more H2O (g) was generated and the formation of Cl2 (g) decreased due to the transition from HCl (g) and Cl2 (g), as a result of which the Pt recovery rate decreased. In addition, this chlorinating roasting had little effect on the Au recovery due to its difficulty to be chlorinated.